Pattern and risk factors of functional limitation and physical disability among community-dwelling elderly in Kuala Pilah, Malaysia: A 12-month follow-up study / Norliana Ismail - Norliana, Ismail (2016)
Functional limitation and physical disability are among the common geriatric conditions that can result in poor health, dependency and institutionalisation. Age-related disability and restriction in the elderly function has become one of the priorities in public health. However, the data on incidence and risk factors associated with functional limitation and physical disability in Malaysia and other developing regions are sparse. Most studies utilized a cross-sectional design which restricts the causal interpretation and inhibits a clear understanding of the relationship between risk factors and occurrence of both conditions. The objectives of this study were; 1) to determine the pattern; in terms of prevalence, incidence and incidence of recovery of functional limitation and physical disability, 2) to identify its associated risk factors, 3) to describe the subtypes of physical disability among community dwelling elderly in Kuala Pilah, Malaysia. This was an observational population-based cohort study with a twelve months follow-up. The study was conducted in Kuala Pilah district, Negeri Sembilan and elderly aged 60 years and above were selected and invited to participate in this study. The data on participants‘ risk factors and physical function status were collected during comprehensive, home-based assessments, which were completed at baseline and twelve months of follow-up. Disability was assessed during three monthly telephone interviews. Beside their socio-demographic characteristics, other risk factors assessed included depressive symptomology, cognitive impairment, social support level, self-reported visual impairment, history of fall and anthropometry measures. Outcome measures were assessed at twelfth months using validated tools for physical disability (Katz Activity of Daily Living and Instrumental Activity of Daily Living) and functional limitation (4-metre walking speed test). The overall prevalence of functional limitation was 62.8%, Instrumental Activity of Daily Living disability was 32.7% and Activity of Daily Living disability was 7.1%. The incidence of functional limitation at iv twelve months of follow-up was 38.4%, IADL disability was 24.8% and ADL disability was 4.8%. The common risk factors for incidence of functional limitation and physical disability were elderly women, advancing age and low educational level. The incidence of recovery from functional limitation at twelve months of follow-up was 31.5%, IADL disability was 34.2% and ADL disability was 43.9%. The most common disability subtype was short term disability, followed by transient disability, long-term disability and recurrent disability. The prevalence and incidence of functional limitation and IADL disability were common among elderly in Kuala Pilah, Malaysia. The prevalence and incidence of ADL disability were lower compared to elderly populations in developed countries. The findings from this study had provided clearer understanding on the relationship between specific impairments and risk factors to the development of functional limitation and physical disability. Specific prevention and early therapeutic interventions can now be outlined in order to optimise function and reduce the disability among elderly.